SPINAL STENOSIS IN FAMILIAL TRANSTHYRETIN AMYLOIDOSIS. Issue 11 (14th October 2015) - Carr, Aisling; Evans, Matthew; Pelayo-Negro, Ana; Shah, Sachit; Choi, David; Blake, Julian; Phadke, Rahul; Gilmore, JD; Hawkins, PN; Reilly, Mary
Abstract : Background: Transthyretin-associated amyloidosis (ATTR) is the commonest cause of hereditary amyloidosis. Age at onset is 50–60 years with average life-expectancy of 7–14 years. Lumbar spinal stenosis also presents in late middle-age; related to disc degeneration, spondylolisthesis and age-related degenerative processes, such as WT-TTR amyloid deposition. Mutant-TTR has not been described in this scenario. Recent therapeutic developments in ATTR, with disease modifying potential, make histological evaluation clinically relevant. Case: Family history prompted screening in an asymptomatic female carrier (heterozygous I84S) at age 42. At age 47 she developed sensory disturbance and pain in the left leg, brought on by exercise and relieved by rest. One year on, exercise tolerance <100 meters and she had sphincter disturbance. Examination revealed decreased pinprick sensation in the L5 dermatome and asymmetry of ankle and knee jerks, pulses were present. A disc bulge at L2/3 with superimposed narrowing of the lumbar canal due to ligamentum flavum hypertrophy was seen on MRI. Immunohistochemistry labelled ATTR deposits in the excised connective tissue. There was neurological improvement post-operatively but amyloid-symptoms qualified her for inclusion in ATTR treatment trials. Discussion: We recommend histological examination for amyloid on tissue from spinal decompression and TTR gene analysis if this is positive.